Prerequisite programs as a means of increasing the safety of production processes - Darmohrai, Alina; Kuzmin, Oleg; Mykhailova, Olga (My University, 2023)
У статті розглянуто роль програм-передумов як ключових елементів для забезпечення гігієнічних умов і зменшення потенційних загроз безпеці у виробничих процесах ресторанів, що сприяє ефективному впровадженню НАССР

The paper highlights the role of prerequisite programs as essential components for ensuring hygienic conditions and mitigating potential safety hazards in restaurant production processes, facilitating effective HACCP implementation
Keywords: кафедра технології ресторанної і аюрведичної продукції; програми-передумови; НАССР; безпечність харчових продуктів; ресторанна індустрія; виробничі процеси; prerequisite programs; food safety; restaurant industry; production processes